2008
DOI: 10.1590/s0100-204x2008001100011
|View full text |Cite
|
Sign up to set email alerts
|

Identificação e validação de marcadores microssatélites ligados ao gene Rpp5 de resistência à ferrugem-asiática-da-soja

Abstract: Resumo -O objetivo deste trabalho foi identificar novos marcadores microssatélites, ligados ao gene Rpp5 de resistência à ferrugem-da-soja, e validar os marcadores previamente mapeados, para que possam ser utilizados em programas de seleção assistida por marcadores moleculares (SAM). Para tanto, uma população F 2 com 100 indivíduos, derivada do cruzamento entre a PI 200526 e a cultivar Coodetec 208, suscetível à ferrugem, foi artificialmente infectada e avaliada quanto à sua reação de resistência à ferrugem. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(16 reference statements)
0
8
0
5
Order By: Relevance
“…Recentemente, no Brasil, diversos trabalhos têm sido realizados para se conhecer os mecanismos de resistência à ferrugem-asiática-da-soja, sejam estes qualitativos (Santos et al, 2007;Silva et al, 2007;Costa et al, 2008;Laperuta et al, 2008;Morceli et al, 2008) ou quantitativos (Koga et al, 2008;Ribeiro et al, 2009aRibeiro et al, , 2009bCruz et al, 2011). A associação de mecanismos qualitativos, por meio da piramidação de genes de resistência, e de mecanismos quantitativos, de resistência horizontal, deve ser utilizada como estratégia dos programas de melhoramento de soja, para que se possa obter resistência mais duradoura.…”
Section: Iniciadorunclassified
“…Recentemente, no Brasil, diversos trabalhos têm sido realizados para se conhecer os mecanismos de resistência à ferrugem-asiática-da-soja, sejam estes qualitativos (Santos et al, 2007;Silva et al, 2007;Costa et al, 2008;Laperuta et al, 2008;Morceli et al, 2008) ou quantitativos (Koga et al, 2008;Ribeiro et al, 2009aRibeiro et al, , 2009bCruz et al, 2011). A associação de mecanismos qualitativos, por meio da piramidação de genes de resistência, e de mecanismos quantitativos, de resistência horizontal, deve ser utilizada como estratégia dos programas de melhoramento de soja, para que se possa obter resistência mais duradoura.…”
Section: Iniciadorunclassified
“…One way to minimize the damage caused by this disease is to use resistant varieties, obtained in breeding programs (Alvarenga et al, 2011). In this context, plant genome sequencing and identification of molecular markers associated with resistance have been used to assist breeding programs (Morceli et al, 2008;Alvarenga et al, 2011). Among the statistical methods based on molecular markers, genome wide selection (GWS) is a technique that has been widely used for selecting materials with higher performance based on information from molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…Five genes for ASR resistance have already been identified, as Rpp1 -PI 200492 (McLean and Byth 1980), Rpp2 -PI 230970 (Bromfield and Hartwig 1980), Rpp3 -PI 462312 Hartwig 1980, 1983), Rpp4 -PI 459025 (Hartwig 1986) and Rpp5 (Parker et al 1993, Grant et al 2000, Hayes et al 2000, Graham et al 2002, Morceli et al 2008. All these genes confer vertical resistance for only some races of P. pachyrhizi and the resistance conferred by these genes has already been broken in most soybean crop regions in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…All these genes confer vertical resistance for only some races of P. pachyrhizi and the resistance conferred by these genes has already been broken in most soybean crop regions in Brazil. However, it was shown that the markers linked to gene Rpp5 are useful in the assisted selection, in early stages of plant development and pathogen absence, which streamlines the most promising genotypes selection (Morceli et al 2008).…”
Section: Introductionmentioning
confidence: 99%